Penggunaan Input yang Optimal pada Usaha Tani Kedelai (Suatu Kasus di Desa Sukahurip, Kecamatan Pangatikan, Kabupaten Garut, Jawa Barat) - Eti Suminartika (Jurnal Ilmu Pertanian Indonesia, 2020)
The majority of soybean supply is fulfilled by importation and the import of soybean tends to increase. The dependency of Indonesia on imported soybean indeed becomes a serious issue in maintaining food security and local production of soybean is low and quite decreasing. The low domestic soybean production might be caused by the inappropriate used of inputs. Many cases found in the field are the inefficient uses of input factors. The purpose of this study is to analyze the factors influencing the soybean production and to analyze the optimal level of input use in soybean production. The study was conducted in the Sukahurip Village, Pangatikan Sub-District, Garut District, West Java in July 2018. The research method used was a survey method. The data used consisted of primary and secondary data. Primary data were obtained from samples of soybean farmers and samples of farmers were taken by a simple random sampling. The data were analyzed by Cobb Douglass`s Production function (to analyze factors affecting soybean production) and the NPM that was equal to BKM formula was used to determine the optimal level of inputs use. Factors influencing soybean production are land and seeds. Land use, seeds, and ZA fertilizer have not been used efficiently because of the limited land use and the use of substandard inputs. The addition of inputs to the optimal level is 1.36 hectares of land use and 52.7 kg of seeds that will maximize the profits. Keywords: efficiency, input, optimal, production, soybean